THE EFFECTIVENESS OF HEALTH EDUCATION ON THE ELDERLY TOWARDS INCREASED ELDERLY VISITS TO THE POSYANDU FOR THE ELDERLY NEW MARKET IN THE WORK AREA OF THE UPTD HEALTH CENTER BASERAH (Al Insyirah International Scientific Conference on Health, 2021)
The aging process is a process that occurs in someone aged 60 years and over which the process is the final stage of his life phase. Based on an initial survey conducted by researchers of 10 elderly people, 8 of them said they did not make a visit to the elderly Posyandu. The purpose of this study was to look at the Effectiveness of Health Education in the Elderly towards Increased Elderly Visits to the Posyandu of the Pasar Baru Elderly in the Work Area of ​​the UPTD Health Center in Baserah. Type of experimental research, pretest and posttest group design research design. This research was conducted in the Work Area of ​​the UPTD Health Center Baserah. The population in this study were all elderly aged 45 - 59 years who were in the Posyandu Elderly Pasar Baru Work Area Health Center UPTD Baserah with a target number of 182 elderly people, the number of samples 126 people. The number of elderly visits before being given health education is 41 people and after being given health education increased to 113 people. The results of the statistical test are the effectiveness of health education in the elderly towards increasing elderly visits with a value (p value = 0,000). It is recommended that the results of this study be a guideline for health workers to be able to apply it in the field and be more active in providing health education to the elderly to increase the interest of the elderly to come to posyandu
Keywords: Health education; Elderly Visitation